Drug therapy problems identified among older adults placed in a nursing home: the Croatian experience. Issue 6 (June 2020) - Šola, Katarina Fehir; Mucalo, Iva; Brajković, Andrea; Jukić, Ivona; Verbanac, Donatella; Vladimir Knežević, Sanda
Objective: The aim of this study was to determine the frequency and type of drug therapy problems (DTPs) in older institutionalized adults. Method: We conducted a cross-sectional observational study from February to June 2016 at a 150-bed public nursing home in Croatia, where comprehensive medication management (CMM) services were provided. A rational decision-making process, referred to as the Pharmacotherapy Workup method, was used to classify DTPs. Results: Data were prospectively collected from 73 residents, among which 71% were age 75 years or older. The median number of prescribed medications per patient was 7 (2–16) and polypharmacy (> 4) was recorded for 54 (74.0%) patients. A total 313 DTPs were identified, with an average of 4.3 ± 2 DTPs per patient. The most frequent DTP was needing additional drug therapy (n = 118; 37.7%), followed by adverse drug reaction (n = 55; 17.6%). Lactulose (14.4%), tramadol (6.7%), and potassium (6.4%) were the medications most frequently related to DTPs. Conclusion: The high prevalence of DTPs identified among older institutionalized adults strongly suggests the need to incorporate new pharmacist-led CMM services within existing institutional care facilities, to improve the care provided to nursing home residents.